2010
DOI: 10.1097/brs.0b013e3181e7fc0a
|View full text |Cite
|
Sign up to set email alerts
|

“The Fly”: A New Clinical Assessment and Treatment Method for Deficits of Movement Control in the Cervical Spine

Abstract: The Fly method provides reliable and valid measures for movement control of the cervical spine. Higher means and wider LOA across patterns and subject groups are reasoned to be inherent in the new Fly method and the subject groups tested. The wide LOA in the symptomatic groups supports the development of a normative database. The new Fly method can be used both as an assessment and a treatment method and ensures gradual progression in the treatment for deficits of movement control in patients with neck pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 21 publications
5
69
1
2
Order By: Relevance
“…The current study also demonstrated differences with respect to motion smoothness (NVP) and symmetry (TTPP). (Vikneet al, 2013, Kristjansson and Oddsdottir, 2010, Sarig Bahat et al , 2014a In the current study however, difference in NVP was unexpectedly higher, rather than lower, in the control subjects and was in contrast to our previous research. It had been hypothesized that normal smooth motion would consist of only one velocity peak.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The current study also demonstrated differences with respect to motion smoothness (NVP) and symmetry (TTPP). (Vikneet al, 2013, Kristjansson and Oddsdottir, 2010, Sarig Bahat et al , 2014a In the current study however, difference in NVP was unexpectedly higher, rather than lower, in the control subjects and was in contrast to our previous research. It had been hypothesized that normal smooth motion would consist of only one velocity peak.…”
Section: Discussioncontrasting
confidence: 81%
“…In the current study neck movement accuracy was found to be impaired in the neck pain group by measuring the accumulated error between a moving target and the participant's moving head following that target. Neck motion accuracy has been studied previously using other methodologies and found to be impaired in patients with neck pain (Kristjansson andOddsdottir, 2010, Woodhouseet al, 2010a). Current findings are in agreement with these previous studies which seem to enhance the value of this measure in clinical assessment of patients with neck pain.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…Neck pain patients may have delayed onset of deep neck flexors [4], increased activation of superficial neck flexors [5], jerky movement patterns [6], decreased cervical flexor endurance [7], lower movement velocity [8][9][10], decreased cervical muscle strength [11], reduced trajectory movement control [12], irregular and stiffer movement patterns [13,14], increased postural sway [15,16], and reduced joint position sense [17][18][19]. However, no single parameter stands out as representing motor dysfunction in the neck and studies typically use a subset of variables that vary between studies [17,20].…”
Section: Introductionmentioning
confidence: 99%